Nitrogen and noble gas data for springs, fumaroles, basalts, and various crustal gases - Labidi, Jabrane; Barry, Peter; Bekaert, David; Broadley, michael; Marty, Bernard; Giunta, Thomas; Warr, Oliver; Sherwood Lollar, Barbara; Fischer, Tobias; Avice, Guillaume; Caracausi, Antonio; Ballentine, Christopher; et al. (IEDA: EarthChem Library, 2020)
Abstract: We use the rare 15N15N isotopologue of N2 as a novel tracer of air contamination in volcanic gas effusions. By constraining air contamination in gases from Iceland, Eifel (Germany), and Yellowstone (USA), we derive new estimates for mantle d15N (fractional difference in 15N/14N from air), N2/36Ar and N2/3He. Other Description: Labidi, J., Barry, P., Bekaert, D., Broadley, M., Marty, B., Giunta, T., Warr, O., Sherwood Lollar, B., Fischer, T., Avice, G., Caracausi, A., Ballentine, C., Halldorson, S., Kurz, M., Kohl, I., Young, E., (2020), "Hydrothermal 15N15N abundances constrain the origins of mantle nitrogen", Nature,(accepted manuscript)